Insular Iconographies Essays in Honour of Jane Hawkes. - Boulton, Meg.; Bintley, Michael (Woodbridge : Boydell & Brewer, Incorporated, 2019)
Essays on aspects of iconography as manifested in the material culture of medieval England.
Introduction; Recutting the Cross: The Anglo-Saxon Baptismal Font at Wilne; The Fountain Sealed Up in the Garden Enclosed: A Vine Scroll at Kells; The Art of the Church in Ninth-Century Anglo-Saxon England: The Case of the Newent Cross; The Stones of the Wall Will Cry Out: Lithic Emissaries and Marble Messengers in Andreas ; Conversion, Ritual, and Landscape: Streoneshalh (Whitby), Osingadun, and the Anglo-Saxon Cemetery at Street House, North Yorkshire; Outside the Box: Relics and Reliquaries at the Shrine of St Cuthbert in the Later Middle Ages; An Unusual Hell Mouth in an Old Testament Illustration: Understanding the Numbers Initial in the Twelfth-Century Laud Bible; The Problem of Man, Carved from the Same Stone; Glass Beads: Production and Decorative Motifs; Unmasking Meaning: Faces hidden and Revealed in Early Anglo-Saxon England; Alcuin, Mathematics and the Rational Mind; Looking down from the Rothbury Cross: (Re)Viewing the Place of Anglo-Saxon Art; Bibliography of Jane Hawkes' Writings; Index; Tabula Gratulatoria
Description based upon print version of record.
JSTOR
Keywords: Art, Irish -- Themes, motives; Art, Anglo-Saxon -- Themes, motives; Material culture -- Ireland -- History -- To 1500.; Material culture -- Great Britain -- History -- To 1500.; Art irlandais -- Thèmes, motifs; Art anglo-saxon -- Thèmes, motifs; ART / European; Art, Anglo-Saxon -- Themes, motives; Material culture; Great Britain; Ireland; To 1500; History